Central Bank Reserve Management Practices : Insights into Public Asset Management - World Bank (World Bank, Washington, DC, 2021)
The World Bank Treasury’s Reserve Advisory and Management Partnership (RAMP) conducted its third survey on reserve management practices in 2021. One hundred and nineteen central banks, from different regions, income groups, and reserve levels, contributed to the survey, which included questions on investment policies, asset allocation, risk management, environmental, social, and governance (ESG) investing, and business continuity. The pandemic underlined the importance of safety and liquidity for reserve portfolios. The authors find that central banks maintained their conservative investment approach, focusing on high-quality fixed-income assets denominated in US dollars and euros. At the same time, against a backdrop of ultra-low interest rates in major economies, we also observe that central banks continued, in their search for yield, to gradually diversify their reserves into more currencies and asset classes within fixed income. Survey results also indicate that central banks’ risk management practices show room for improvement, especially in institutions that have expanded into nontraditional asset classes, including those that invest in corporate credit. Meanwhile, reserve managers could further enhance internal risk and reporting practices to strengthen oversight. ESG investing is still rarely adopted by central banks, and fewer than a quarter of respondents have included ESG objectives in their investment policy. Crucially, this is largely explained by the focus of reserve portfolios on high-quality fixed-income assets, among which ESG instruments and strategies are rarely encountered. We learn that, in order to maintain business continuity, central banks implemented home-based work in 2020, but technological drawbacks and cybersecurity concerns tended significantly to obstruct any ambition to attain fully remote reserve management operations. The paper carries the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Bank for Reconstruction and Development and World Bank and its affiliated organizations or those of the Executive Directors of the World Bank or the governments they represent.